Impacts of AD-Related ABCA7 and CLU Variants on Default Mode Network Connectivity in Healthy Middle-Age Adults - Zhang, Xin Yuan; Wang, Yun Fei; Zheng, Li Juan; Zhang, Han; Lin, Li; Lu, Guang Ming; Zhang, Long Jiang (Frontiers in Molecular Neuroscience, 2020)
Objective: To investigate the impact of AD-related risk gene (ABCA7 and CLU) on the functional connectivity pattern of default mode network (DMN) in healthy middle-age adults. Methods: 147 healthy middle-aged volunteers were enrolled in this study. All subjects completed MRI scans, neuropsychological assessments, and AD-related genotyped analysis. All subjects were divided into high, middle and low risk groups according to the score of risk genotypes, which were derived by integrating CLU (rs11136000, rs2279590, rs9331888, rs9331949) and ABCA7 (rs3764650 and rs4147929). The genetic effects of CLU, ABCA7, and CLU x ABCA7 on DMN functional connectivity pattern were explored. Finally, correlation analysis was performed between the signals of brain regions with genetic effect and neuropsychological test scores. Results: Compared with the low-risk group, the high-risk group of CLU showed decreased functional connectivity in PCC and the left middle frontal cortex (P<0.05, GRF correction). As for the interaction between the CLU and ABCA7, all the subjects were divided into high, middle and low risk group; the middle-risk group was divided into CLU and ABCA7-dominated middle-risk group. The function connectivity pattern of DMN among the three or four groups were distributed in the bilateral medial prefrontal cortex (MPFC) and bilateral superior frontal gyrus (SFG) (P<0.05, GRF correction). When APOEε4 carriers were excluded, The CLU-predominant middle-risk group displayed the decreased functional connectivity in MPFC when compared with the low-risk group, while ABCA7-prodominant middle-risk group displayed decreased activity in cuneus when compared with the high-risk group (P<0.05, GRF correction). The z values of left middle frontal cortex were positively correlated with the scores of serial dotting test in high-risk group of CLU, while z values of MPFC and cuneus were positively related to the scores of MoCA in low-risk group of three or four groups. Conclusions: The functional connectivity of MPFC-PCC might be modulated by the interaction of CLU and ABCA7; Moreover, APOEε4 might be interacted with ABCA7 and CLU modulation in the middle-aged carriers.